2013
DOI: 10.1016/j.acmx.2013.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors in a Mexican middle-class urban population. The Lindavista Study. Baseline data

Abstract: These data show a population with a high-risk profile, secondary to the agglomeration of several cardiovascular risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 38 publications
5
23
0
2
Order By: Relevance
“…The present findings clearly demonstrate that MetS is more prevalent among obese adults (73.7%) when compared with overweight (58.0%) and normal weight adults (36.7%). A significant prevalence was observed for all components of the syndrome, which were higher for the obese with respect to overweight and normal weight people from Nuevo León, with similar percentages to those reported in a previous study analysing cardiovascular risk factors in a Mexican urban population (The Lindavista Study) [25]. The prevalence of abdominal obesity was evidenced by the elevated number of obese or overweight people, reaching 97.5% in the obese and 83.5% in overweight adults.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The present findings clearly demonstrate that MetS is more prevalent among obese adults (73.7%) when compared with overweight (58.0%) and normal weight adults (36.7%). A significant prevalence was observed for all components of the syndrome, which were higher for the obese with respect to overweight and normal weight people from Nuevo León, with similar percentages to those reported in a previous study analysing cardiovascular risk factors in a Mexican urban population (The Lindavista Study) [25]. The prevalence of abdominal obesity was evidenced by the elevated number of obese or overweight people, reaching 97.5% in the obese and 83.5% in overweight adults.…”
Section: Discussionsupporting
confidence: 85%
“…Abdominal obesity is associated with insulin resistance, hyperinsulinaemia, and increased risk of type 2 diabetes and vascular problems [26]. An interesting parameter to highlight was the high incidence of low HDL-cholesterol, which was also previously observed among Mexican population [25]. Moreover, more than half of the subjects had elevated triglyceride levels, a fact that might be inversely associated with HDL-cholesterol, which has been previously described [27].…”
Section: Discussionmentioning
confidence: 74%
“…Moreover, in a prior Mexican survey (ENSANUT 2006) performed around the same time as CARMELA, the reported frequency of hypertension was 31.6% [Barquera et al 2010]. In a sample of 2602 middle class urban subjects in Mexico City, the frequency of hypertension was 32% [Meaney et al 2013], which is similar to the percentage found in the ENSANUT survey but almost three times higher than in the CARMELA study.…”
Section: The Problem Of Information About Hypertension In the Lac Regionsupporting
confidence: 63%
“…Para ello, es necesario abarcar distintos tipos de poblaciones de tal forma que las acciones preventivas sean más eficientes. En el presente estudio no se presentaron diferencias en cuanto a la incidencia de HTA, 29 % para la comunidad rural y 24 % para la urbana; cifras consistentes con las reportadas en otras investigaciones en Venezuela y América Latina (17)(18)(19)(20). Sin embargo, investigaciones peruanas encontraron que la prevalencia de HTA no alcanza el 20 % y que, a diferencia de la similitud entre comunidades encontrada en el presente estudio, la prevalencia de HTA en la población urbana es mayor que en la población rural (21).…”
Section: Discussionunclassified